1989
DOI: 10.1161/01.cir.80.6.1805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a critical coronary stenosis on myocardial neutrophil accumulation during ischemia and early reperfusion in dogs.

Abstract: In many experimental models of ischemia and reperfusion, reperfusion is performed abruptly, allowing full reactive hyperemia to occur. In the clinical setting, however, reperfusion after thrombolysis is often limited by residual stenosis. Some experimental models attempt to mimic this situation with a "critical stenosis" (defined as a coronary constriction sufficient to abolish reactive hyperemia without altering baseline flow). The purpose of this study was to determine whether preventing reactive hyperemia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Myocardial edema and an increase in tissue plasma proteins have been reported previously after either reversible or irreversible ischemic injury of myocytesl, 19,36 and as observed previously, were transmural even though the myocyte necrosis was primarily in the subendocardial half of the ischemic region. These changes presumably indicate functional and/or anatomic changes in the microvasculature, but the precise mechanism of such microvascular injury is unknown.…”
Section: Effect Ofanti-cd18 Antibody On Myocardial Edemasupporting
confidence: 76%
See 1 more Smart Citation
“…Myocardial edema and an increase in tissue plasma proteins have been reported previously after either reversible or irreversible ischemic injury of myocytesl, 19,36 and as observed previously, were transmural even though the myocyte necrosis was primarily in the subendocardial half of the ischemic region. These changes presumably indicate functional and/or anatomic changes in the microvasculature, but the precise mechanism of such microvascular injury is unknown.…”
Section: Effect Ofanti-cd18 Antibody On Myocardial Edemasupporting
confidence: 76%
“…The protocol for isolation and labeling of PMNs was that of Richard et al, 19 with several modifications. These modifications have resulted in improved PMN survival upon readministration of the labeled cells to the dogs, as indicated by a higher cell-associated/total bloodindium ratio, and a longer circulating half-life of the labeled cells compared with our earlier studies.…”
Section: Isolation And`1in-labeling Of Pmnsmentioning
confidence: 99%
“…However, we have recently observed that the number of neutrophils that progressively accumulate in the reperfused myocardium and are a major proposed source of superoxide radicals, and also of infarct size, was not affected by the presence or absence of a critical stenosis at the onset of reperfusion. 34 Finally, it must be considered that a small therapeutic effect might not be detected in the relatively small number of dogs used per group in the present study. To evaluate this possibility, we have analyzed our results after enlarging the control group by including the control dogs from our preceding study.…”
Section: Infarct Sizementioning
confidence: 84%